MODIFICATION OF THE COMPRESSION STRENGTH OF A STRUCTURAL CONCRETE PLACED UNDER WATER WITH VARIOUS AMOUNTS OF ANTI-WASHOUT ADDITIVE - Irigoín Idrogo, Harlyn Jhóssender; Mosqueira Moreno, Miguel Angel; Mosqueira Ramírez, Hermes Roberto (LACCEI, 2024)
The research consists of determining the modification of the compressive strength of a structural concrete placed underwater, with various amounts of anti-washout additive. The investigation was carried out by comparing a standard concrete of f’c 280 kg/cm2 dry cast, with the (3) designs that contain additive in 260 ml, 780 ml and 1300 ml per 100 kg weight of cement of anti-washout additive MasterMatrix® UW 450, placed underwater. To carry out the tests, cylindrical concrete specimens were made that were then tested in compression at ages of 7, 14 and 28 days; the unit weight of the concrete in the fresh state was also measured. The results obtained were that the higher the content of anti-slide additive, the modification of the compressive strength is greater, obtaining a decrease of 21.10%, 45.06% and 45.90% for the additions of 260 ml, 780 and 1300 ml per 100 kg of cement weight. respectively, while for the same dosages the unit weight of the concrete in the fresh state presents a decrease of 1.27%, 2.61% and 2.96% compared to the standard concrete.